An implicit slicing method for additive manufacturing processes - D. Adams; C. J. Turner (Virtual and Physical Prototyping, 2018)
All additive manufacturing processes involve a distinct pre-processing stage whereby the part geometry is translated into a process-specific printing plan. This plan is developed in layers or slices of the original part geometry by a set of algorithms collectively known as a slicer. Most commercial slicing programmes generate tool paths explicitly and do not consider the impact of resulting geometric part features (e.g. thin walls, small corners, round profiles) which can result in critical voids leading to part failure. Recent work into an implicit slicing algorithm allows for an infinite set of functionally defined infill patterns to be defined. When these patterns are overlaid onto each part layer, the mechanical properties of the part and the presence undesirable voids and flaws can be reduced or eliminated. The variation of part properties is demonstrated with tensile tests of dog-bone specimens with different infill patterns to determine their resulting mechanical properties.